A priori consent within pragmatic randomised controlled trials: a web-based survey of statin use in primary care. Issue 4 (23rd September 2017) - Semprini, Alex; Hills, Thomas; Braithwaite, Irene; Weatherall, Mark; Beasley, Richard
Abstract : Background: Clinical research methodology is evolving with the advent of pragmatic randomised controlled trials (PRCTs). Novel approaches for informed consent in PRCTs are needed. Objective: To explore public opinion about different ways of giving informed consent for PRCTs. Design: Web-based survey assessing acceptability of three PRCT consent scenarios for statin use. Setting: Community-based study. Participants: 678 (12%) adults responded to an open-access web-based survey. Measurements: Participant-rated acceptability of three different options for giving informed consent for a PRCT testing two commonly prescribed, effective treatments: statins for hyperlipidaemia. Option A was written informed consent given a priori for a specific study, with verbal confirmation of consent at time of randomisation. Option B was written informed, general consent a priori for multiple comparative effectiveness studies, with verbal confirmation for a specific study at time of randomisation. Option C was written informed consent for a specific study at time of randomisation. Results: Acceptability was higher for option A (475/529 (89.9%)) and B (441/487 (90.6%)) compared with C (339/481 (70.5%)). The estimates of differences in paired proportions were A versus C, 19.4% (95% CI 14.4 to 24.5), p<0.001; B versus C, 20.1% (95% CI 15.2 to 25.0), p<0.001. Limitations: The study design may have been subject to cognitive biases such as framing and anchoring effects. The anonymised web-based survey allowed no follow-up or verification for missing data. The sampling frame used an institutional database and social media and selection bias and halo effects may have been present. The 12.3% response rate may represent poor generalisability. Conclusion: The concept of giving a priori consent, with subsequent confirmation at time of randomisation in a PRCT, was more favourable than the traditional model of consent in a general-practice-based study of statin use.